Current Status of Obstetric Anaesthesia: Improving Satisfaction and Safety - J Sudharma Ranasinghe; David Birnbach (Indian Journal of Anaesthesia, 2009)
The Centers for Disease Control and Prevention (CDC) reported in 2003 that although the maternal mortal-ity rate has decreased by 99% since 1900, there has been no further decrease in the last two decades [1] . A more recent report indicates a rate of 11.8 per 100,000 live births [2] , although anaesthesia-related maternal mortality and morbidity has considerably decreased over the lastfew decades. Despite the growing complexity of problems and increasing challenges such as pre-existing maternal disease, obesity, and the increasing age of pregnant mothers, anaesthesia related maternal mortality is extremely rare in the developed world. The current safety has been achievedthrough changes in training, service, technical advances and multidisciplinary approach to care. The rates of general anaesthesia for cesarean delivery have decreased and neuraxial anaesthetics have become the most commonly used techniques. Neuraxial techniques are largely safe and effective, but potential complications, though rare, can be severe.